Eldest - Paolini, Christopher (New York : Alfred A. Knopf, 2005)
After successfully evading an Urgals ambush, Eragon is adopted into the Ingeitum clan and sent to continue his "Dragon Rider" training so he can assist the Varden in their struggle against the Empire.
Keywords: Fantasy; Dragons -- Fiction; Youths' writings; Fiction